2006
DOI: 10.1016/j.ygeno.2006.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Novel genes identified by manual annotation and microarray expression analysis in the pancreas

Abstract: The mouse PancChip, a microarray developed for studying endocrine pancreatic development and diabetes, represents over 13,000 cDNAs. After computationally assigning the cDNAs on the array to known genes, manual curation of the remaining sequences identified 211 novel transcripts. In microarray experiments, we found that 196 of these transcripts were expressed in total pancreas and/or pancreatic islets. Of 50 randomly selected clones from these 196 transcripts, 92% were confirmed as expressed by qRT-PCR. We eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…For Affymetrix-based assays, present/marginal/absent calls from the MAS4/MAS5 software were used to determine whether a transcript was expressed. For Panc Chips, a P (present) call was made if the signal for the gene reporter of interest was above 90% of the blanks on the array (Mazzarelli et al, 2006). For each of the 13 genes in the LKB1 target list that were represented on the arrays, P and A calls were collected for each gene reporter in each assay so that at least seven independent calls were available.…”
Section: Methodsmentioning
confidence: 99%
“…For Affymetrix-based assays, present/marginal/absent calls from the MAS4/MAS5 software were used to determine whether a transcript was expressed. For Panc Chips, a P (present) call was made if the signal for the gene reporter of interest was above 90% of the blanks on the array (Mazzarelli et al, 2006). For each of the 13 genes in the LKB1 target list that were represented on the arrays, P and A calls were collected for each gene reporter in each assay so that at least seven independent calls were available.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier expression studies with cDNA libraries from mouse and human pancreatic tissues, and gene arrays identified approximately 10,000 to 14,000 transcripts expressed in mouse and human pancreatic islets, respectively . Further microarray studies as well as massive parallel sequencing analyses of isolated islets, and cultured islet cells were used to establish more comprehensive lists of transcripts that are characteristic for mouse, rat and human pancreatic islets .…”
Section: Diversity Of Current Methods For Isolating Pancreatic Isletsmentioning
confidence: 99%
“…Gene expression in islets of Langerhans is profoundly sensitive to human β-cells [14]. As all these variants in totum account for only about 10% of the genetic variance of type 2 diabetes [12,15,16], it is highly likely that many more risk variants, either rare or common, remain to be identified. Thus, studying the transcriptome of β-cells in response to a diabetogenic dietary challenge might provide important insights into the regulation of the known genes, as well as illuminate other possible candidates.…”
Section: Introductionmentioning
confidence: 99%
“…Computational annotation is applied to the human and mouse DoTS transcripts (5,6), including Entrez Gene (7) assignment and coding potential, and the annotations are included in EPConDB. DoTS annotation was instrumental in the discovery of novel mouse transcripts, expressed in the pancreas (6). DoTS transcripts are assembled to preserve alternative transcripts, so it is possible to have more than one DoTS transcript associated with a particular gene.…”
Section: Contentmentioning
confidence: 99%